2006
DOI: 10.1080/01926230601042494
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Cytotoxic and Carcinogenic Activities of Systemically Distributed Organic Chemicals

Abstract: Toxicity and carcinogenicity in the mucosa of the nasal passages in rodents has been produced by a variety of organic chemicals which are systemically distributed. In this review, 14 such chemicals or classes were identified that produced rodent nasal cytotoxicity, but not carcinogenicity, and 11 were identified that produced nasal carcinogenicity. Most chemicals that affect the nasal mucosa were either concentrated in that tissue or readily activated there, or both. All chemicals with effects in the nasal muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 266 publications
(430 reference statements)
1
12
0
Order By: Relevance
“…Prilo formed a relatively high level of MA-derived DNA adduct in the liver, but no adduct was detected in UBE DNA in prilo-or MA-dosed or multidose groups, suggesting that MA is mainly bioactivated in the liver. The enzyme activities for both cytochrome P450 and sulfotransferase are the highest in the liver (DeBaun et al, 1970;Guengerich and Liebler, 1985), which is consistent with the relatively high adduct yield at this site (Gonçalves et al, 2001;Jeffrey et al, 2002Jeffrey et al, , 2006. The absence of MA adducts in the NM may indicate that the tissue concentration or metabolism of MA is different from DMA in the NM.…”
Section: Duan Et Alsupporting
confidence: 62%
See 2 more Smart Citations
“…Prilo formed a relatively high level of MA-derived DNA adduct in the liver, but no adduct was detected in UBE DNA in prilo-or MA-dosed or multidose groups, suggesting that MA is mainly bioactivated in the liver. The enzyme activities for both cytochrome P450 and sulfotransferase are the highest in the liver (DeBaun et al, 1970;Guengerich and Liebler, 1985), which is consistent with the relatively high adduct yield at this site (Gonçalves et al, 2001;Jeffrey et al, 2002Jeffrey et al, , 2006. The absence of MA adducts in the NM may indicate that the tissue concentration or metabolism of MA is different from DMA in the NM.…”
Section: Duan Et Alsupporting
confidence: 62%
“…This indicates, as have other studies (Jeffrey et al, 2006), that formation of adducts is insufficient for carcinogenicity. Prilo formed a relatively high level of MA-derived DNA adduct in the liver, but no adduct was detected in UBE DNA in prilo-or MA-dosed or multidose groups, suggesting that MA is mainly bioactivated in the liver.…”
Section: Duan Et Almentioning
confidence: 57%
See 1 more Smart Citation
“…Identification of metabolic functions of nasal epithelia has sparked considerable interest in the morphology of the nasal passages, and consequently, the recognition of chemically induced lesions has become more commonplace in recent years (Bond 1986;Dahl 1986;Reed 1993;C. Keenan, Kelly, and Bogdanffy 1990;Adams et al 1991;Jeffrey, Iatropoulos, and Williams 2006). In addition, there has been considerable recent interest in transport of toxicants into the brain via the olfactory nerves (Dorman et al 2002;Harkema, Carey, and Wagner 2006).…”
Section: Nasal Cavitymentioning
confidence: 98%
“…Other studies revealed that 4MI produced alveolar/bronchiolar adenoma and carcinoma in male and female mice (Cunha et al 2011). Hepatic histiocytosis, hepatocellular eosinophilic, and mixed cell foci in male and female rats were also noted (Jeffrey, Iatropoulos, and Williams 2006). However, the mechanisms underlying the 4MI-induced toxicity of 4MI is not known.…”
Section: Introductionmentioning
confidence: 95%